analisis reputasi alyasina hermawan di platform linkedin sebagai personal branding digital - Rama Gusti Thabrany Prasetya; Ahmad Taufiq Maulana Ramdan (Penerbit Jurnal Indonesia, 2026)
This study examines the self-presentation strategy of Alyasina Hermawan in building a digital reputation as a Human Resources professional on LinkedIn through a qualitative single-case study combining profile observation, digital activity documentation, and in-depth interviews (October–November 2025). Grounded in the premise that professional personal branding is shaped by the quality of digital signals and network structures, the research analyzes key variables profile optimization, content consistency, and selective networking along with the mediating mechanisms of visibility and credibility that lead to recruitment outcomes. The findings indicate that optimizing profile elements (professional photo, informative headline, and evidence-oriented summary) enhances initial credibility; selective and relevant content curation strengthens competency claims without requiring high posting frequency; and strategically built networks function as effective amplification channels to influential professional audiences. The synergy of these three pillars generates meaningful exposure and job offers through passive recruitment mechanisms, demonstrating that digital reputation is formed not by posting intensity but by signal quality and network relevance. In conclusion, passive personal branding that emphasizes alignment between claims and evidence, message consistency, and strategic networking is effective in establishing a credible professional reputation on LinkedIn, offering practical implications for non-celebrity professionals.